(untitled) (Osney Mead, Oxford, 1999)
Provides an invaluable overview of the subject for students taking courses in ecotoxicology and environmental pollution, as well as wider degree programmes in biology, ecology, wildlife management, environmental science, sanitation engineering and related subjects. Softcover. DLC: Pollution--Environmental aspects
Độc chất học thủy vực,Độc chất học sinh thái
Keywords: Pollution; Environmental aspects